Linear amyopathic dermatomyositis with calcinosis cutis responsive to topical sodium thiosulfate. Issue 4 (28th May 2019) - Topham, Christina; Haynes, Dylan; Frigerio, Alice; Hull, Christopher
Abstract: A case of a 15‐year‐old male patient with a 3‐year history of linear, segmental amyopathic dermatomyositis with calcinosis cutis is presented. The calcinosis was recalcitrant to treatment with topical steroids and hydroxychloroquine. Topical 10% sodium thiosulfate use for 8 weeks resulted in improvement. The use of topical sodium thiosulfate for patients in whom surgical extraction is not an option is detailed.